History of mountain Jews of the North Caucasus region 1920s – 1930s: current issues in historiography and sources - Dmitriy Vladimirovich Sen (Кавказология, 2023)
The article analyzes historiographical and source research problems associated with the study of the past of Mountain Jews of the North Caucasus region. The achievements of recent Russian historiography related to scientists’ various degrees of attention to one or more local Mountain Jewish groups are evaluated. The scientific issues presented in the essay are also linked to key events in the lives of Mountain Jews, most notably the resettlement programs implemented by the Soviet government during this time period. They resulted in a shift in the spatial distribution of Mountain Jews on North Caucasus area in the 1920s and early 1930s. It is known that the Mountain Jews of the 1920s and 1930s were researched more fragmentarily than the turn of the nineteenth and twentieth centuries, as well as since the 1940s - second half of the twentieth century. The prospects for renewing the source base on the research issue are highlighted, including the entrance of new sources into scientific circulation, such as clerical sources from various Soviet, party, and other bodies.